Green Expectations: Hamilton in the 1890s - Grant, Matthew (Architectural History Aotearoa, 2023)
In August 1889, Hamilton celebrated its twenty-fifth anniversary of European settlement. A public holiday was declared, flags flew from several flagstaff, and the old Fourth Waikato veterans paraded. Despite the fanfare, expectations were low for the decade ahead. Prosperity in Hamilton was hampered by its inland isolation, the lack of profitable natural resources, and poor returns from land investment. The town’s establishment was as a military outpost and its strategic advantage offered little to settlers who struggled to make a living. Hamilton’s main street had the unflattering appearance of an American Frontier Town. Waikato soil was naturally unproductive. Farming in the Waikato had originally been a mixture of grain and other crops, cattle for its meat, and sheep for wool. Waikato’s reputation for abundant and profitable dairy was some years away. The fortunes of Hamilton would change for the better in the late 1890s. Scientific breakthroughs in soil research, new farming techniques, the introduction of refrigerated freight, and improved global prices for meat and dairy products, would all lead to prosperity in the region. This paper will examine the context and circumstances that shaped Hamilton’s difficult years leading up to the 1890s, influenced for better or worse by its landscape, and the prosperity that would eventually arrive by the end of the decade.